Educational Innovation in Human Capital Ecosystem to Boot Indonesia’s Digital Investment Appeal - Gunawan Tjokro; Zaenuri Zaenuri; Heri Yanto; Fathur Rokhman; Abdul Rajagukguk (The Journal of Educational Development, 2025)
The quality of human capital is a key determinant in attracting foreign direct investment (FDI), especially within high-technology sectors where innovation, adaptability, and workforce readiness are critical. Despite having a vast digital consumer base, Indonesia has failed to attract investment from global technology leaders such as Apple, signaling deeper structural challenges within its human resource (HR) ecosystem. This study aims to investigate how HR-related constraints including competency gaps, misalignment between education and industry, and ineffective incentive policies, influence multinational investment decisions. Employing a qualitative case study approach, the research integrates netnographic observations with thematic content analysis. Primary data were obtained from Apple's digital narratives, social media platforms, and credible electronic mass media, and triangulated with academic literature and national policy documents. The findings reveal that Indonesia’s fragmented HR development strategies, limited curriculum flexibility, and weak institutional coordination reduce its appeal in the global FDI landscape. These challenges indicate an urgent need for education system reform, workforce absorption enhancement, and policy synchronization across sectors. The study contributes theoretically by combining digital ethnography with institutional analysis and provides practical implications for developing countries seeking to foster a sustainable, knowledge-based economy. In conclusion, aligning human capital development with global industry demands is essential to increasing FDI competitiveness.